How to Make Perfect Snow - Koptyug, Andrey; Ananiev, Leonid; Äström, Johan (Institutionen för teknik, fysik och matematik, 2006)
“To the North Pole with own snow?” This kind of natural first reaction can be expected from the readers recollecting Andersen’s immortal ‘Snow Queen’, especially when they find out that the authors are living and working in central Sweden, about 500 km north of Stockholm (the altitude corresponding to the point about 100 kilometers north of Anchorage, Alaska). And it almost inevitably will be followed by, “Is 1 m of snow not enough?” Actually, the answer is, “It depends…” If you are digging your car out in the cold morning after a heavy snowfall for a third time in a week, even 5 cm of snow, sure thing, is more than enough. But if you are waiting till mid-January to put on your beloved downhill gear and to get to the favorite slope, and then outdoor temperature drops below —25° С and stays like this till mid-April, after which the snow melts in a week, let’s see what you would say… So, it should not be surprising that there is someone willing to pay for the thing falling from the Heavens ‘for free’. And, consequently, there are people who make the equipment for ‘manufacturing’ snow. When using proper snowmaking equipment, alpine ski resorts, including the ones in Siberia and central Sweden, extend he season up to four months (two in early winter and two in spring). And these are commonly the best four months for skiing, not too cold and not too warm — perfect for a family outing. Popular science paper ordered by the Journal popularizing science and published by Siberian Branch of Academy of Sciences (Novosibirsk, Russia)